Serum autoantibodies against hexokinase 1 manifest secondary to diabetic macular edema onset - Šimčíková, Daniela; Ivančinová, Jana; Veith, Miroslav; Dusová, Jaroslava; Matušková, Veronika; Němčanský, Jan; Kunčický, Přemysl; Chrapek, Oldřich; Jirásková, Naďa; Gojda, Jan; Heneberg, Petr (Diabetes research and clinical practice, 2024)
AIMS: Autoantibodies against hexokinase 1 (HK1) were recently proposed to be associated with diabetic macular edema (DME). We hypothesized that anti-HK1 autoantibodies can be used as DME markers and to predict DME onset. MATERIALS AND METHODS: Serum from patients with 1) DME, 2) diabetes mellitus (DM), 3) allergies or autoimmunities, and 4) control subjects was tested for anti-HK1 and anti-hexokinase 2 (HK2) autoantibodies by immunoblotting. Patients with DM were prospectively followed for up to nine years, and the association of anti-HK1 antibodies with new-onset DME was evaluated. The vitreous humor was also tested for autoantibodies. RESULTS: Among patients with DME, 32 % were positive for anti-HK1 autoantibodies (42 % of those with underlying type 1 DM and 31 % of those with underlying type 2 DM), and 12 % were positive for anti-HK2 autoantibodies, with only partial overlap of these two groups of patients. Anti-HK1 positive were also 7 % of patients with DM, 6 % of patients with allergies and autoimmunities, and 3 % of control subjects. The latter three groups were anti-HK2 negative. Only one of seven patients with DM who were initially anti-HK1 positive developed DME. CONCLUSIONS: Anti-HK1 autoantibodies can be used as DME markers but fail to predict DME onset.
Keywords: senioři; Glycolysis; Macular Edema; Hexokinase; diabetes mellitus 1. typu; Disease marker; Middle Aged; mužské pohlaví; Diabetes Mellitus, Type 2; makulární edém; Prospective Studies; Adult; Diabetic Retinopathy; diabetes mellitus 2. typu; Tissue damage; Diabetes Mellitus, Type 1; Disease prediction; ženské pohlaví; Humans; prospektivní studie; Autoimmunity; biologické markery; autoprotilátky; lidé středního věku; dospělí; Biomarkers; Vitreous fluid; Female; hexokinasa; Aged; diabetická retinopatie; Autoantibodies; lidé; Male